POSHAN's abstract digest on maternal and child nutrition research - Issue 32 - Avula, Rasmi (International Food Policy Research Institute, 2020)
We are delighted to present the first issue of Abstract Digest for this year. It has a collection of articles on various outcomes, determinants and interventions related to maternal and child nutrition, from around the world and India, in particular. In this issue, we feature a special series on the double burden of malnutrition from The Lancet journals and three systematic reviews – 1. Micronutrient supplementation and fortification interventions and health and developmental outcomes; 2. Effectiveness of interventions for managing acute malnutrition among children below five years; and 3. Preventive interventions among adolescents. In addition, there are two unique global articles relevant for multiple contexts – the first one generates lessons about nutrition behaviour change from cluster-randomized evaluations in three countries, Bangladesh, Vietnam, and Ethiopia; and the second is based on research to improve nutrition in the context of an at-scale social protection program in Mexico, which has learnings for many developing countries. Given below is the list of articles included in this issue. Please click on the title if you wish to go straight to the article or scroll down to explore the abstract in the pages that follow.